RELATIONSHIP WITH FRIENDS AND EXPECTANCY OF NURSING HOME USE IN THE HEALTH AND RETIREMENT STUDY - Lim, E (Innov Aging, 2018)
Little is known whether relationship with friends acts as a push or pull factor for future nursing home use based on Wiseman’s Behavioral Model of Elderly Migration (Wiseman, 1980). Using the 2014 Health and Retirement Study (HRS) dataset, this study looked at the association between relationship with friends and expectation of nursing home use in the future among U.S. older adults aged 65 and older. There were 3,772 respondents who completed the 2014 HRS Leave-Behind Questionnaire. Their average age was 75.26 years old, with the majority being female (58.7%), non-Hispanic White (78.3%), married (61.1%) and have a child (94.6%). Results indicated that negative relationship with friends was significantly associated with the expectation of nursing home use in the next five years among older adults (RRR = 1.258, p = 0.035). However, no significant relationship between positive relationship with friends and expectation of nursing home use in the future was found. Models were controlled for respondents age, gender, race/ethnicity, education, household income, marital status, child status, self-rated health, Activity of Daily Living (ADL), and Medicaid status. Therefore, our findings indicated that older adults who did not enjoy good relationship with their friends were more likely to expect the use of nursing homes in the future.